Production, optimization, characterization and storage stability of roselle concentrate - Anvarali, Mohamed Nazim (2013)
Three different extraction techniques were used to determine the suitability and efficiency of the roselle extraction techniques for the development of roselle concentrate. These extraction techniques were 1) hot water extraction (HWE), 2) puree extraction (PE) and 3) osmotic extraction (OE). Data from preliminary comparative studies suggested that the osmotic solution (OS) from the OE technique can be used for the development of roselle concentrate as it has a significantly (p<0.05) higher anthocyanin content, Dmalic and L-malic acid with the value of 100.00 ± 0.43 mg/L as expressed in delphinidin-3-glucoside, 4043.60 ± 11.17 and 2946.90 ± 16.69 (ppm/L); respectively, compared to HWE and PE. Further studies were conducted using response surface methodology (RSM) in order to determine the optimal processing parameters of the OE technique. The parameters affecting the roselle extraction process were optimized for the color of the roselle concentrate (red purplish), a taste with minimum sharpness and a high anthocyanin content. A central composite design (CCD) with a quadratic model consisted of three independent variables: extraction time, osmotic solution concentration and extraction temperature. The response variables were used to determine the Hunter lab color index – L*, a*, b*, acidity percentage, total anthocyanin content, color density, color degradation index and sensory attributes, which included the color, grassy (odor), fruity (taste), sharpness (taste) and overall acceptability of all of the roselle concentrates and juices. A total of 20 different combinations (including six replicates of the center point each with coded value 0) were chosen at random according to a Central Composite Design (CCD) configuration for three factors. The results suggested that for the production of red to purple color of roselle concentrate, the extraction should be carried under the following conditions: 70 °C (extraction temperature), 205 minutes (extraction time) and 62.5 °Brix of sucrose solution (as a medium of extraction). Meanwhile, the storage temperature yielded significant (p<0.05) negative effects on the total quality of the roselle concentrate when compared to the duration of storage. High temperatures during storage may cause dramatic changes in anthocyanin content and the color of the osmotic solution due to the degradation of anthocyanins. Roselle concentrate stored for 8 weeks at 5 °C retains up to 74.8% of its total anthocyanin content (compared to the initial value; 4334.15 mg/L); these values are significantly (p<0.05) higher than those of roselle concentrate that were stored at 25 °C and 45 °C (31.1% and 6.5% of its initial anthocyanin content at the end of storage, respectively). This research shows that the osmotic solution, which is normally not reused and is considered as industrial waste in the fruit osmotic dehydration (OD) process, exhibits the highest amount of total anthocyanin (p<0.05). The osmotic solution may be used as an ingredient as a healthy roselle concentrate. Proper storage at low temperature can ensure its appearance and taste qualities, and the functional properties of the concentrate will be stabilized, which will allow roselle juice to be accepted as a functional drink.